The prediction of multiaxial fatigue probabilistic stress–life curve by using fuzzy theory. Issue 2 (4th May 2017) - Li, Bochuan; Jiang, Chao; Han, Xu; Li, Yuan
Abstract: The fuzziness of the traditional multiaxial fatigue prediction model is discussed and the fuzzy theory is applied into fatigue reliability analysis. The fuzzy linear regression analysis method is used to determine the fuzzy coefficients in the multiaxial stress–life equation under a small sample condition, and the corresponding multiaxial fatigue probabilistic stress–life curve is calculated with different confidence levels.